# How do you differentiate #y=e^((2x)/3)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate ( y = e^{(2x/3)} ), you would use the chain rule, which states that if ( y = f(g(x)) ), then ( \frac{{dy}}{{dx}} = f'(g(x)) \cdot g'(x) ).

First, find the derivative of the outer function ( e^u ), which is ( e^u ) itself. Then, find the derivative of the inner function ( u = \frac{2x}{3} ), which is ( \frac{2}{3} ).

So, the derivative of ( y = e^{(2x/3)} ) is ( \frac{2}{3} \cdot e^{(2x/3)} ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7